2020
DOI: 10.1097/dcr.0000000000001656
|View full text |Cite
|
Sign up to set email alerts
|

Family History Is Associated With Recurrent Diverticulitis After an Episode of Diverticulitis Managed Nonoperatively

Abstract: BACKGROUND: To date, the impact of family history on diverticulitis outcomes has been poorly described. OBJECTIVE: This study aims to evaluate the association between family history and diverticulitis recurrence after an episode of diverticulitis managed nonoperatively. DESIGN: This is a retrospective cohort study with prospective telephone follow-up. SETTINGS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Alternatively, they might see the long-term sequelae of smoldering symptoms or complicated disease and seek surgical treatment to avoid the experience of a family member. Another possibility is that surgeons are more likely to recommend colectomy for those with a family history, either due to recent literature demonstrating an association between family history and recurrence 12,14 or perhaps because family history predisposes individuals to disease characteristics unmeasured in the present study, such as smoldering symptoms or outpatient recurrence. Because elective surgery substantially reduces the risk of recurrence, 39,40 it is also possible that the increased use of surgery among those with a family history played a significant role in decreasing recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, they might see the long-term sequelae of smoldering symptoms or complicated disease and seek surgical treatment to avoid the experience of a family member. Another possibility is that surgeons are more likely to recommend colectomy for those with a family history, either due to recent literature demonstrating an association between family history and recurrence 12,14 or perhaps because family history predisposes individuals to disease characteristics unmeasured in the present study, such as smoldering symptoms or outpatient recurrence. Because elective surgery substantially reduces the risk of recurrence, 39,40 it is also possible that the increased use of surgery among those with a family history played a significant role in decreasing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In a US-based, single-center analysis, Hall et al demonstrated an increased risk of recurrent diverticulitis (HR 2.2; 95% CI 1.4–3.2) among individuals with a family history of diverticulitis as defined by retrospective medical record review. 12 In a study at 2 Canadian centers, Almalki et al 14 demonstrated that a patient-reported family history of diverticulitis was associated with recurrence (HR 3.74; 95% CI 2.67–5.24). Participants in both studies were more likely to experience recurrence (36% and 37%, respectively), which may be due to inclusion of outpatient diverticulitis episodes as recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Additional phenome-wide association studies were undertaken that showed genetic enrichment of mesenchymal stem cells and other connective cell and tissue types. Patients with a family history of diverticulitis have also been noted to be at higher risk for recurrent and complicated episodes, though the potential genetic underpinning of this finding has not been specifically investigated [ 17 ]. The milieu of pathophysiologic factors that may cause diverticulitis is summarized in Fig.…”
Section: Etiology Of Diverticulitismentioning
confidence: 99%
“…Outside of these rare syndromes and families however, diverticulitis typically occurs sporadically in otherwise healthy patients. However, even among typical diverticulitis patients, family history is an independent risk factor for disease recurrence and diverticular complications 23 .…”
Section: Diverticulitis and Mendelian Traitsmentioning
confidence: 99%